Mental Well-being among Health and Non-Health Majoring M.Phil. Students Kathmandu, Nepal - Thapa , Ramesh (HPE Forum, 2026)
Mental well-being is a critical part of overall health, particularly for students pursuing higher education, as they navigate various academic, social, and personal challenges. The study aimed to assess the mental well-being among health-majoring and non-health-majoring Mphil students in Kathmandu, Nepal. A descriptive, cross-sectional, study was carried out among 32 health majoring and non-health majoring MPhil students. Sample was selected by using non-probability, purposive sampling method. Data were collected through online self-administered questionnaire and analyzed it in descriptive statistics using Statistical Package for the Social Science (SPSS) version 25. The findings disclose that health-majoring students exhibit significantly better mental well-being, with 81.8% practicing daily self-care and lower reported academic stress. In contrast, non-health-majoring students report higher academic stress and less frequent self-care practices. Additionally, health-majoring students exhibit higher self-assessed understanding of mental health concepts and greater comfort in discussing mental health issues compared to their non-health counterparts. While most of the respondents (81.2%) feel good about their mental health, there are differences between groups when it comes to managing stress and knowing about mental health. This study shows that learning about health can improve mental well-being. It helps people handle stress better, take care of themselves, and understand mental health issues. These findings emphasize the need for integrating mental health promotion strategies into university curricula, mainly for non-health disciplines, to enhance students' mental well-being and equip them with skills to navigate academic and personal challenges effectively.